Versatile formation of supported lipid bilayers from bicellar mixtures of phospholipids and capric acid - Sut, Tun Naw (2021)
Originally developed for the structural biology field, lipid bicelle nanostructures composed of long- and short-chain phospholipid molecules have emerged as a useful interfacial science tool to fabricate two-dimensional supported lipid bilayers (SLBs) on hydrophilic surfaces due to ease of sample preparation, scalability, and versatility. To improve SLB fabrication prospects, there has been recent interest in replacing the synthetic, short-chain phospholipid component of bicellar mixtures with naturally abundant fatty acids and monoglycerides, i.e., lauric acid and monocaprin. Such options have proven successful under specific conditions, however, there is room for devising more versatile fabrication options, especially in terms of overcoming lipid concentration-dependent SLB formation limitations. Herein, we investigated SLB fabrication by using bicellar mixtures consisting of long-chain phospholipid and capric acid, the latter of which has similar headgroup and chain length properties to lauric acid and monocaprin, respectively. Quartz crystal microbalance-dissipation, epifluorescence microscopy, and fluorescence recovery after photobleaching experiments were conducted to characterize lipid concentration-dependent bicelle adsorption onto silicon dioxide surfaces. We identified that uniform-phase SLB formation occurred independently of total lipid concentration when the ratio of long-chain phospholipid to capric acid molecules (“q-ratio”) was 0.25 or 2.5, which is superior to past results with lauric acid- and monocaprin-containing bicelles in which cases lipid concentration-dependent behavior was observed. Together, these findings demonstrate that capric acid-containing bicelles are versatile tools for SLB fabrication and highlight how the molecular structure of bicelle components can be rationally finetuned to modulate self-assembly processes at solid–liquid interfaces.